Sustainable Food Agricultural Community: the Dialectic of Neoliberalism and Local Governance in Merauke, South Papua - Tonny, Fredian; Kolopaking, Lala Mulyowibowo; Kinseng, Rilus A; Muljono, Pudji; Satria, Arif (Jurnal AGRISEP, 2026)
Merauke's 2025 Community Paddy Field Expansion (CSR) is a strategic policy to expand rice fields outside Java to achieve food self-sufficiency in Indonesia. This study aims to examine how the development of sustainable food farming communities is shaped by the dialectic between local and neoliberal food governance in Merauke's 2025 CSR. Using a critical qualitative approach and a multi-level case study method in three of the 46 villages implementing Merauke's 2025 CSR, this study analyzes the interaction between state rationality and local governance in three socio-ecological types of villages. Qualitative primary data processed and analyzed through data condensation revealed that the implementation of Merauke 2025 CSR in three socio-ecological types of village communities created an antagonistic landscape between the former transmigrant village communities and the indigenous farming communities (native Papuans). Within this antagonistic landscape, the development of sustainable food farming communities is shaped by a negotiated interaction between central government policies with neoliberal governance and local community practices that lead to sustainable governance.